ANALISIS PERBEDAAN SIKAP KONSUMEN ATAS RETAIL MIX BERDASARKAN DEMOGRAFI (STUDI KASUS PADA KONSUMEN MINIMARKET TEAM MART JOMBANG) - lailatus sa'adah (JoEMS (Journal of Education and Management Studies), 2019)
This study has a purpose; 1) know the strategy mix minimarket team mart; 2) to know differences in consumer attitudes over retail mix based on demography (gender, age and income). This type of research is quantitative with the minimarket consumer population of Team Mart of 9,471 people. The sample in this study were 100 respondents. Data analysis in the research using attitude scale and one way anova. The results of this study show; 1) there is no difference of consumer attitude toward retail mix based on demography that is based on gender with probability value 0.259, 2) there is no difference of consumer attitude toward retail mixbased on age with value significance 0.093 and 3) there is no difference of consumer attitude toward retail mix based on income with significance value 0.259. Keywords: consumer attitude over retail mix.